Efficacy of metabolites of a Streptomyces strain (AS1) to control growth and mycotoxin production by Penicillium verrucosum, Fusarium verticillioides and Aspergillus fumigatus in culture - Mohd Danial, A.; Medina, Angel; Sulyok, Michael; Magan, Naresh (Springer, 2020)
The objectives of this study were to determine the efficacy of metabolites of a Streptomyces strain AS1 on (a) spore germination, (b) mycelial growth, (c) control of mycotoxins produced by Penicillium verrucosum (ochratoxin A, OTA), Fusarium verticillioides (fumonisins, FUMs) and Aspergillus fumigatus (gliotoxin) and (d) identify the predominant metabolites involved in control. Initial screening showed that the Streptomyces AS1 strain was able to inhibit the mycelial growth of the three species at a distance, due to the release of secondary metabolites. A macroscopic screening system showed that the overall Index of Dominance against all three toxigenic fungi was inhibition at a distance. Subsequent studies showed that the metabolite mixture from the Streptomyces AS1 strain was very effective at inhibiting conidial germination of P. verrucosum, but less so against conidia of A. fumigatus and F. verticillioides. The efficacy was confirmed in studies on a conducive semi-solid YES medium in BioScreen C assays. Using the BioScreen C and the criteria of Time to Detection (TTD) at an OD = 0.1 showed good efficacy against P. verrucosum when treated with the Streptomyces AS1 extract at 0.95 and 0.99 water activity (aw) when compared to the other two species tested, indicating good efficacy. The effective dose for 50% control of growth (ED50) at 0.95 and 0.99 aw were approx. 0.005 ng/ml and 0.15 μg/ml, respectively, with the minimum inhibitory concentration (MIC) at both aw levels requiring > 40 μg/ml. In addition, OTA production was completely inhibited by 2.5 μg/ml AS1 extract at both aw levels in the in vitro assays. Ten metabolites were identified with four of these being predominant in concentrations > 2 μg/g dry weight biomass. These were identified as valinomycin, cyclo(L-Pro-L-Tyr), cyclo(L-Pro-L-Val) and brevianamide F.
Keywords: Streptomycetaceae; Antifungal metabolites; Fungal pathogens; In vitro efficacy; Mycotoxins; Germination; Mycelial growth